PENGARUH TINGKAT PENDIDIKAN, PEMAHAMAN AKUNTANSI, MOTIVASI DAN UMUR USAHA TERHADAP PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL MENENGAH (SAK EMKM) PADA KOTA PEKANBARU (Studi Empiris pada UMKM di Kota Pekanbaru) - Romy Eka Putra A; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. However, MSMEs have various problems especially in terms of recording financial statements. The Government has disclosed the Financial Accounting Standards of Micro Small Medium Enterprises in 2016 as a guide for the preparation of simpler financial statements making it easier in preparing financial reports in accordance with the standards. The purpose of this study is to determine the effect of education level, understanding of accounting, motivation and age of business on the application of Accounting Standards of Micro Small Medium Enterprises to MSMEs. The population of this research is all owners of MSMEs in Pekanbaru City. Sampling technique with accidental sampling, based on the technique obtained by respondents as much as 100 MSMEs. Data collection technique is by using questioner, collected data is analyzed by using descriptive analysis and multiple regression analysis. From the results of descriptive analysis, it is found that the average implementation of Accounting Standards of Micro Small Medium Enterprises in MSMEs in Pekanbaru City in the criteria is quite low, the average education level of SMA, and the average business life of 1 to 10 years. The result of the research shows that the understanding of accountancy and motivation has a positive effect on the application of Accounting Standards of Micro Small Medium Enterprises to MSMEs. While the level of education and age of business does not affect the application of Accounting Standards of Micro Small Medium Enterprises to MSMEs. Suggestions that can be given are among others MSMEs expected to prepare financial report in accordance with Accounting Standards of Micro Small Medium Enterprises, as well as related parties that can provide socialization of Accounting Standards of Micro Small Medium Enterprises.Keywords : Accountability, Village Financial Management, Village Government